Altered gait parameters in distracted walking: a bio-evolutionary and prognostic health perspective on passive listening and active responding during cell phone use - Bazzi, Hassan; Cacace, Anthony T. (Frontiers in Integrative Neuroscience, 2023)
The underpinnings of bipedal gait are reviewed from an evolutionary biology perspective to better understand relevant issues and concerns while individuals are ambulating and using a cell phone. The historical record and associated adaptive changes dating back over millions of years, indicate that gait, locomotion, and migration across various geographical regions influenced the development of language, played a distinctive role in the enhancement of culture, and contributed to the advancement of knowledge through social interactions and verbal discourse. Herein, the designation of those tempo-spatial variables most vulnerable to distraction and interference effects is highlighted in normal adults. This information is noteworthy since deficits in this area can have prognostic implications leading to the risk-of-falling, the detection of metabolic and neurological disease, and have strong associations with cognitive decline, dementia, and mortality. This information was explored in twenty-one healthy young adults without hearing, vestibular, balance, otological or neurological dysfunction using a computerized walkway combined with specialized software algorithms to extract gait parameters. Overall, this work serves as a foundation for predicting and potentially averting gait-related disturbances that may occur in older adult populations. Emphasizing the use of quantifiable gait parameters in medical, psychological, and audiological examinations is advocated.